Intravenous Ondansetron Versus Intravenous Nalbuphine in Reducing Intrathecal Fentanyl Induced Pruritus During Cesarean Delivery : A Randomized Controlled Trial - Tipu, Md Rezaul Hoque; Chowdhury, Gulshan Ara; Billah, KM Baki; Khatoon, Syeda Nafisa; Khan, Shameema Hossain (Journal of Chittagong Medical College Teachers’ Association, 2017)
Background: This prospective, randomized, double-blinded study wasundertaken to compare the effectiveness and side effects of intravenous Ondansetron and Nalbuphine in the reduction of intrathecal Fentanyl-induced pruritus in obstetric patients of Chittagong Medical College Hospital. Materials and methods : This study was done in CMCH during the period August 2012 to January 2014. One hundred and thirty women of ASA status I or II undergone caesarean section by spinal anesthesia using Inj. Bupivacaine 10 mg and Inj. Fentanyl 15 μgm was randomly allocated in two groups, by simple random method. The patients received Nalbuphine 4mg or Ondansetron 8mg as intravenous injection in respective of groups, immediately after the baby was delivered and umbilical cord was clamped. Onset of pruritus, the degree of pruritus, four-point rating score for nausea and vomiting were assessed and recorded as per case record form and preserved for analysis. All statistical analysis was performed using SPSS® software package version SPSS-16 (SPSS, Chicago, Illinois, USA) for windows XP. pvalue was considered statistically significant when it was less than 0.05(p£0.05). Results : Intravenous Ondansetron was more effective in reducing the incidence of fentanyl-induced pruritus than Nalbuphine. Pruritus was mild and relatively short duration in most patients. Patients remained hemodynamically stable after using both Ondansetron and Nalbuphine. Conclusion: Ondansetron is more effective and cheaper than Nalbuphine in reducing the intrathecal Fentanyl induced pruritus during cesarean delivery and safely used as an alternative to expensive drug Inj. Naloxone. JCMCTA 2017 ; 28 (1) : 45 - 51